CP invariance of chiral gauge theories and Majorana-Yukawa couplings on the lattice - Igarashi, Yuji; Pawlowski, Jan M. (Arxiv, 2009)
The construction of CP-invariant lattice chiral gauge theories and the construction of lattice Majorana fermions with chiral Yukawa couplings is subject to topological obstructions. In the present work we suggest lattice extensions of charge and parity transformation for Weyl fermions. This enables us to construct lattice chiral gauge theories that are CP invariant. For the construction of Majorana-Yukawa couplings, we discuss two models with symplectic Majorana fermions: a model with two symplectic doublets, and one with an auxiliary doublet.
Gesehen am 05.12.2017